Study of Socio – Personal Profile and Awareness of Rural Women Regarding ICDS Activities in the Faizabad District of U.P - Garima Tiwari , P. Singh and Pinaki Roy, (Indian Journal of Extension Education, 2017)
The study was conducted in Milkipur block of Faizabad district by interviewing a total of 100 respondents whowere selected through proportionate random sampling technique. The study depicted that the highest number ofrespondents (59%) were found in the age category of 22 to 32 years belonging to joint families (62%) and having 5to 8 members in their families (54%). The scheduled caste respondents were more in comparison to other categoriesof caste. The scientific orientation was observed of low level while value orientations and risk were observed ofmedium level. The contact of respondents with Auxiliary Nurse Midwife among formal sources, family membersamong informal sources and radio was observed important among mass media. Agriculture was observed as mainfamily occupation of the respondents (55%) having annual income of upto Rs. 40000 (40%). An overwhelmingmajority of the respondents were found using cell phone as their main source of communication.